CELEBRITY ENDORSER, DAYA TARIK IKLAN, BRAND AWARENESS DAN BRAND ATTITUDE - Devi Farela; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2014)
Advertising is one of the most common promotional tool used by companies to inform,persuade, and increasing the target buyer or society. Currently the development of advertisingon television is very fast, is the largest telecom products in advertising spending. The rise oftelecommunication service advertising on television is linked to the consumer to figure outwhat the ad. The products promoted through media advertising can affect brand awareness.This study using SEM analysis. The population in this study were students UndiknasUniversity Denpasar. While the sample in this study amounted to 124 people who had seen theprovider XL commercials on television with the NOAH version method used in this study isthat accidental sampling nonprobability sampling.These results indicate that the variable Celebrity Endorser Attractiveness Advertisingpositive and significant effect on the variable Brand Awareness and Brand Awarenesssubsequent positive and significant effect on the variable Brand Attitude. Thus advertising ontelevision provider should pay attention to the ads that are witnessed by consumers canincrease brand awareness and consumer attitudes toward the brand.Keywords: Celebrity Endorser, Attractiveness Advertising, Brand Awareness, and BrandAttitude.